Trifluoperazine Effect on Erythrocyte Hemolysis in Electrolyte Hypertonic Solutions - Shpakova, N. M.; Dunaevskaya, O. N.; Synchikova, O. P.; Bondarenko, V. A. (Problems of Cryobiology and Cryomedicine, 2002)
Manifestation of antihemolytic activity of trifluoperazine (TFP) during hypertonic hemolysis of erythrocytes depends on temperature and state of cells. Both the reduction of temperature down to 0Â°C and preliminary incubation of cells in presence of 0.7 M NaCl result in decrease of antihemolytic activity of trifluoperazine at the removal of cells into 4.0 M NaCl. Combined action of low temperature and preliminary dehydration are accompanied by inversion of the effect of the amphiphile and supplementary lysis of cells in 4.0 M NaCl. Cell treatment by neuraminidase and proteolytic enzymes does not affect the manifestation of antihemolytic activity of trifluoperazine during hypertonic hemolysis of erythrocytes at 37Â°C, the preliminary dehydration of such kind of cells results in its decrease. Modification of membrane glycoproteins as a result of treatment by proteolytic enzymes is accompanied by increase in antihemolytic activity of trifluoperazine at 0Â°C. The results obtained are discussed from the point of view of processes underlying the formation and stabilization of transmembrane defects. Â